Legal Counseling on Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence as an Effort to Protect Women and Children in Wariori Indah Village - Max Bonsapia; Marwiah’tul Adawiyah Rumkel; Anthon H. Rumbruren; Isak Samuel K. Mans (Abdi Masyarakat, 2026)
Violence against women and children is a human rights violation that requires serious and integrated action. The enactment of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS) is a crucial legal instrument, but its effectiveness is often hampered by low understanding among grassroots communities. This community service activity aims to provide legal education and map the sociological challenges in protecting women and children in Wariori Indah Village, Masni District. The method used was legal counseling through a participatory approach involving interactive dialogue, observation, and focus group discussions with village officials and residents. The results of the activity indicated that the residents of Wariori Indah Village still face fundamental obstacles such as limited knowledge about the spectrum of sexual violence, a strong patriarchal culture that considers violence a private matter, and limited access to information and official complaint services. Through this counseling, there was an increase in collective awareness among residents regarding the importance of reporting through formal channels and the prohibition of resolving sexual violence cases through peaceful/customary channels. The conclusion of this service confirms that the protection of vulnerable groups requires ongoing synergy between educational institutions, village governments, and legal service institutions to create a village environment that is safe and responsive to the rights of women and children.